Pengaruh Pendidikan Kesehatan dan Tingkat Upah Terhadap Produktivitas Tenaga Kerja di Indonesia - Lusy Tania; Syamsul Amar (Jurnal Kajian Ekonomi dan Pembangunan, 2022)
The study examines to analyze the effect of education, health and wage rate to labor productivity in Indonesia. The research uses panel data for the period from 2015 to 2020. Study result: Education and wage rate have a significant and positive effect on the labor productivity in Indonesia. Health have a not significant and negative effect on the labor productivity productivity in Indonesia. Simultaneously, the effect of education, health and wage rate to the labor productivity in Indonesia is significant.